ACCIÓN NEUROTRÓPICA DEL EXTRACTO HIDROALCOHÓLICO DE MELISSA OFFICINALIS (TORONJIL) EN EL COMPORTAMIENTO DEL NIÑO ANSIOSO, CON Y SIN EXPERIENCIA DENTAL. - Pardo-Aldave, Karina (Revista Kiru, 2009)
Objective: To determine the neurotropic action of the hydroalcoholic extract of M. officinalis in the dental behaviour of anxious child patient, with and without dental experience. Material and Method: Double-blind, randomised, controlled trial with the participation of 64 girls from the school Juana Alarco from Dammert (Lima, Peru), 6 years of age, with and without dental experience who presented anxiety, which was diagnosed with evidence of the color and drawing test (colors test and drawing test of the human figure of koppitz). Two groups were formed; the first received a unique dose (2.5 mg/kg) of hydroalcoholic extract of Melissa officinalis (lemon balm) and the second received a placebo. The behaviour of girls during prophylaxis and placebo sealants was evaluated 30 minutes after the administration of the extract or placebo by the Houpt Behavior Rating Scale Result: Statistically significant difference was found between the behaviour and anxiety of girls, with and without dental experience, who received placebo and extract, during the treatment of prophylaxis and sealant (chi-square test, p = 0.000 and Fisher's exact test, p = 0.000 respectively). Conclusion: The dose of 2.5 mg/kg of the hydroalcoholic extract of M. officinalis produces excellent behaviour and low anxiety in the anxious child, with and without experience, in the treatment of prophylaxis and sealant.